Seroprevalence of antibodies against SARS-CoV-2 among health care workers in a large Spanish reference hospital - Garcia-Basteiro, Alberto L.; Moncunill, Gemma; Tortajada, Marta; Vidal, Marta; Guinovart, Caterina; Jiménez, Alfons; Santano, Rebeca; Sanz, Sergi; Méndez, Susana; Llupià, Anna; Aguilar, Ruth; Alonso, Selena; et al. (Nature communications, 2020)
Health care workers (HCW) are a high-risk population to acquire SARS-CoV-2 infection from patients or other fellow HCW. This study aims at estimating the seroprevalence against SARS-CoV-2 in a random sample of HCW from a large hospital in Spain. Of the 578 participants recruited from 28 March to 9 April 2020, 54 (9.3%, 95% CI: 7.1–12.0) were seropositive for IgM and/or IgG and/or IgA against SARS-CoV-2. The cumulative prevalence of SARS-CoV-2 infection (presence of antibodies or past or current positive rRT-PCR) was 11.2% (65/578, 95% CI: 8.8–14.1). Among those with evidence of past or current infection, 40.0% (26/65) had not been previously diagnosed with COVID-19. Here we report a relatively low seroprevalence of antibodies among HCW at the peak of the COVID-19 epidemic in Spain. A large proportion of HCW with past or present infection had not been previously diagnosed with COVID-19, which calls for active periodic rRT-PCR testing in hospital settings. Health care workers (HCW) are a high-risk population for SARS-CoV-2 infection. Here, the authors determine seroprevalence against SARS-CoV-2 in HCWs of a large Spanish reference hospital and find a cumulative prevalence of SARS-CoV-2 infection (presence of antibodies or past or current positive rRT-PCR) of 11%.